One-class classification based on the convex hull for bearing fault detection. (15th December 2016) - Zeng, Ming; Yang, Yu; Luo, Songrong; Cheng, Junsheng
Abstract: Originating from a nearest point problem, a novel method called one-class classification based on the convex hull (OCCCH) is proposed for one-class classification problems. The basic goal of OCCCH is to find the nearest point to the origin from the reduced convex hull of training samples. A generalized Gilbert algorithm is proposed to solve the nearest point problem. It is a geometric algorithm with high computational efficiency. OCCCH has two different forms, i.e., OCCCH-1 and OCCCH-2. The relationships among OCCCH-1, OCCCH-2 and one-class support vector machine (OCSVM) are investigated theoretically. The classification accuracy and the computational efficiency of the three methods are compared through the experiments conducted on several benchmark datasets. Experimental results show that OCCCH (including OCCCH-1 and OCCCH-2) using the generalized Gilbert algorithm performs more efficiently than OCSVM using the well-known sequential minimal optimization (SMO) algorithm; at the same time, OCCCH-2 can always obtain comparable classification accuracies to OCSVM. Finally, these methods are applied to the monitoring model constructions for bearing fault detection. Compared with OCCCH-2 and OCSVM, OCCCH-1 can significantly decrease the false alarm ratio while detecting the bearing fault successfully. Highlights: One-class classification based on the convex hull (OCCCH) is proposed. A generalized Gilbert algorithm is proposed to achieve OCCCH. OCCCH has two different forms, i.e., OCCCH-1 and OCCCH-2. OCCCH performs more efficiently than OCSVM with the SMO algorithm. OCCCH-2 can receive comparable classification accuracies to OCSVM.